Associação entre nódulos pulpares e doenças sistêmicas: um estudo de caso-controle - Romano, Bruna de Souza (2021)
The aim of this study was to evaluate the association between pulp stones (PS) and systemic diseases. With a case-control design, 490 individuals, aged between 18 and 65 years, of both sexes, were included. Panoramic digital radiographs (n = 1047) were accessed from October 2018 to June 2019. A pre-selection was made based on the age range established, so 217 exams were excluded, and 830 (280 controls and 550 cases remained). For the initial distribution in the groups, four trained and calibrated researchers (kappa = 0.88) participated. The controls were those subjects who had all teeth without any suspicion of PS, while the cases presented some suggestive image of PS, which were temporarily classified as suspects. In order to confirm the cases, initially the electronic dental records were accessed in search of radiographic exams that could help; otherwise, the patient was invited to attend the University to undergo a periapical radiographic examination, provided that they met the following inclusion criteria: desire to participate in the research, ability to understand what it was about, possibility of traveling to the exam site, and women could not be pregnant or suspected of being pregnant. In this stage, 340 patients (32 controls and 308 cases) were excluded due to non-compliance with the criteria mentioned above. For the collection of information, a questionnaire was applied by telephone (to all controls and to cases with the possibility of inclusion without the need for a complementary examination in person) or in person (for those who needed to undergo a complementary radiographic examination at the University). The instrument used was composed of demographic variables (observed skin color, gender and age), habits (smoking and frequent use of alcohol) and general health (diabetes - type I or II, regular consultation with a cardiologist, cardiovascular disorders, kidney or gall bladder, and arthritis and / or other autoimmune disease). In search of factors that could be different between genders, women were asked about their regular consultation with the gynecologist, diagnosis of endometriosis or ovarian cyst. The data collection stage was carried out from July to November 2019, by four trained researchers. After the descriptive analysis, the data were submitted to Student's t test to identify differences between cases and controls, in relation to sex and age. For the cross-tabulation, a Chi-square test was performed. The analyzes were performed in SPSS, version 25.0, with a 5% significance level. No differences were found between groups for the variables gender (p = 0.966) and age (p = 0.186). Among the other variables, only the presence of kidney stones was associated with the case group (p = 0.001), being 2.4 times higher in this group compared to the control group. For females, no significant differences were found in relation to whether or not they had PS (p> 0.05). In conclusion, this study revealed the existence of an association between the presence of PS and the probability of an individual having kidney stones.